Bronchiectasis: a case-based approach to investigation and management. (11th July 2018) - Contarini, Martina; Finch, Simon; Chalmers, James D.
Bronchiectasis is a chronic respiratory disease characterised by a syndrome of productive cough and recurrent respiratory infections due to permanent dilatation of the bronchi. Bronchiectasis represents the final common pathway of different disorders, some of which may require specific treatment. Therefore, promptly identifying the aetiology of bronchiectasis is recommended by the European Respiratory Society guidelines. The clinical history and high-resolution computed tomography (HRCT) features can be useful to detect the underlying causes. Despite a strong focus on this aspect of treatment a high proportion of patients remain classified as "idiopathic". Important underlying conditions that are treatable are frequently not identified for prolonged periods of time. The European Respiratory Society guidelines for bronchiectasis recommend a minimal bundle of tests for diagnosing the cause of bronchiectasis, consisting of immunoglobulins, testing for allergic bronchopulmonary aspergillosis and full blood count. Other testing is recommended to be conducted based on the clinical history, radiological features and severity of disease. Therefore it is essential to teach clinicians how to recognise the "clinical phenotypes" of bronchiectasis that require specific testing. This article will present the initial investigation and management of bronchiectasis focussing particularly on the HRCT features and clinical features that allow recognition of specific causes. Bronchiectasis is a heterogeneous disease with diverse clinical presentation. Careful history, review of radiological features and laboratory testing are required to identify the underlying diagnosis. http://ow.ly/RDF730koTxu